Peningkatan Pemahaman Guru Biologi SMA Kota Malang tentang Evolusi Mikroba melalui Teknologi CRISPR dan Mekanisme Resistensi Antibiotik - Jatmiko, Yoga Dwi; Suharjono, Suharjono; Ardyati, Tri; Mustafa, Irfan (J-Dinamika : Jurnal Pengabdian Masyarakat, 2025)
The implementation of Merdeka Curriculum in high school requires Biology teachers to face new challenges in teaching, especially the topic of microbial evolution. Microbes play an important role as a model in understanding the evolutionary process, including through CRISPR technology (genome editing). In addition, the mechanism of antibiotic resistance is also a clear example of evolution through genetic changes. However, limited access to information and facilities is an obstacle for teachers in developing appropriate learning modules. This service activity aims to improve the insight and competence of Biology teachers related to microbial evolution, through the introduction of CRISPR technology and antibiotic resistance, both in theory and practice. The training began with a pre-training survey on antibiotic use, material delivery and continued with antibiotic sensitivity test practice. Evaluation in the form of pretest and posttest was also given to participants who were categorized on a scale of understanding: very low, low, medium, high, and very high. The training participants had sufficient experience in the use of antibiotics before the training, but their understanding of antibiotics still varied. The pretest results obtained an understanding of 8.3% very low, 20.8% low, 33.3% medium, 33.3% high, and 4.2% very high. The posttest results showed a significant difference, with only two categories, 38.1% high and 61.9% very high. This result shows that the participants' understanding has increased by 28.4% with an average pretest score of 62 and posttest score of 87. In addition, participants were also able to conduct antibiotic sensitivity tests and how to interpret the data. The participants' response was very positive, with a satisfaction index score between 94-97 which is classified as very good. The theory and practice obtained are expected to increase teacher innovation in learning for students to understand microbial evolution.